Dynamics and policies of prejudice from the eighteenth to the twenty-first century - Motta, Giuseppe, 1977- (Cambridge Scholars Publishing, 2018)
"Prejudice is a multi-faceted concept that affects the relationships between individuals and groups and the creation of socially formed categories of ideas. It concerns race, religion, gender, social distinctions and political beliefs, and can be considered as a natural human process of out-group homogeneity, as well as the product of an authoritarian context or as a reaction against modernization or other symbolic or realistic threats. This volume defines the dynamics and policies of prejudice in the historical passage between the modern and contemporary age, bringing together articles by different scholars representing various disciplines, which allows an analysis of the different aspects of prejudice. The book includes interesting chapters on anti-Semitism, the ethnic conflicts of the twentieth century, Russia and the Balkans, and gender bias, among other subjects."--